ISLAM DAN PERKEMBANGAN SAINS & TEKNOLOGI (Studi Perkembangan Sains dan Teknologi Dinasti Abbasiyah) - Mochamad Muksin (Universitas Merdeka Malang, 2016)
The development of science and technology will always be attached to the development of the human mind, which means that also the development of science and technology in the Muslim community is also growing in line with the thinking of his people and Islam itself. Abbasid dynasty is a golden peak development of science and technology in the Islamic world for seven khalifa leadership, namely: Al-Mahdi (775-785 AD), Al-Hadi (785-786 AD), Harun al-Rashid (786-809 AD) Al-Ma'mun (813-833 AD), Al-Mu'tasim (833-842 AD), Al-Wasiq (842-847 AD), and Al-Mutawakkil (847-861 AD). In the reign of the Abbasid dynasty produced many works by the leading figures in various fields, such as the work of al-Kindi in philosophy, chemistry and optics. Not to mention the historic scientific books that have been produced by Muslim scientists. In the heyday of the 'Abbasids recorded successfully laid the foundation for the existence and development of science and philosophy that drives the development of world science. DOI: https://doi.org/10.26905/jtmi.v2i1.617